Intrinsic specificity of plain ammonium citrate carbon dots for Helicobacter pylori: Interfacial mechanism, diagnostic translation and general revelation. (June 2022) - Geng, Jiayue; Wang, Zhuangzhuang; Wu, Yanping; Yu, Lejun; Wang, Lili; Dong, Quanjiang; Liu, Chenguang; Chi, Zhe
Abstract: The exploitation of carbon dots (CDs) is now flourishing; however, more effort is needed to overcome their lack of intrinsic specificity. Herein, instead of synthesizing novel CDs, we reinvestigated three reported CDs and discovered that plain ammonium citrate CDs (AC-CDs) exhibited surprising specificity for Helicobacter pylori . Notably, we showed that the interfacial mechanism behind this specificity was due to the affinity between the high abundant urea/ammonium transporters on H. pylori outer membrane and the surface-coordinated ammonium ions on AC-CDs. Further, we justified that ammonium sulfate-citric acid CDs also possessed H. pylori -specificity owing to their NH4 + doping. Thereby, we suggested that the incorporation of a molecule that could be actively transported by abundant membrane receptors into the precursors of CDs might serve as a basis for developing a plain CD with intrinsic specificity for H. pylori . Moreover, AC-CDs exhibited specificity towards live, dead, and multidrug-resistant H. pylori strains. Based on the specificity, we developed a microfluidics-assisted in vitro sensing approach for H. pylori, achieving a simplified, rapid and ultrasensitive detection with two procedures, shortened time within 45.0 ​min and a low actual limit of detection of 10.0 ​CFU ​mL −1 . This work sheds light on the design of more H. pylori -specific or even bacteria-specific CDs and their realistic translation into clinical practice. Graphical abstract: Image 1 Highlights: Plain ammonium citrate CDs have intrinsic specificity for Helicobacter pylori . Affinity of outer-membrane urea receptors to NH4 + on CDs decides the specificity. The specific CDs coupling microfluidics confers a simplified detection of H. pylori . The mechanism and translation inspire the engineering of bacteria-specific CDs.